Penyelesaian Hukum terhadap Perbuatan Melawan Hukum pada Jasa Konstruksi di Indonesia - Tri Vebri Yance (Fakultas Hukum Universitas Riau, 2024)
The implementation of construction work is carried out based on a construction work contract that has been previously agreed upon. The implementation and supervision of construction work, as stated in Article 28 paragraph 1 of Government Regulation Number 29 of 2000 concerning the Implementation of Construction Services, include physical implementation, supervision, testing, and final handover of the work results. The final results of the work encompass the stages of work results, handover results, initial handover results, and final handover results, which must meet the criteria of cost efficiency, quality standards, and timely completion. Numerous cases arise in the final handover of construction work where the building fails to function, either wholly or partially, in terms of technical aspects, utility, safety, and occupational health, or public safety. These failures are often due to the fault of the Service Provider (Developer), referred to as Construction Work Failures and Building Failures. The purpose of this research is to analyze the legal resolution of unlawful acts in construction services in Indonesia and the legal consequences of resolving unlawful acts in construction services in Indonesia. The method employed is sociological legal research. Based on the research findings, the resolution of unlawful acts in construction services in Indonesia should hold the service providers or developers—whether individuals or legal entities—accountable for any construction work and building failures. Construction work and building failures are often associated with parties choosing measures to protect and safeguard their personnel involved rather than addressing the underlying issues. Natural conditions are frequently blamed for construction failures to cover up human negligence and carelessness, which should be held accountable. Disputes arising from construction work and building failures in a build-operate agreement between construction service providers and users can be resolved through formal processes, such as adjudication, including court proceedings and arbitration, or informal processes based on the agreement of the disputing parties through negotiation and mediation. The legal consequences of resolving unlawful acts in construction services in Indonesia indicate that losses incurred due to unlawful acts entitle the victims to demand compensation from the perpetrators through legal claims. Specifically, for unlawful acts resulting from construction failures, court rulings often oblige the responsible parties to compensate for the losses, either by restoring the damaged building or providing monetary compensation.